Clinical and Medicolegal Evaluation of Inhalation Injury Cases in the Forensic Process - Emre Yuluğ; Demet Polat Yuluğ (Turkish Journal of Forensic Medicine, 2026)
Aim: This study aimed to retrospectively evaluate the demographic, clinical, and medicolegal characteristics of inhalational exposure cases referred for forensic medical evaluation. It also aimed to examine the distribution of selected clinical findings and medicolegal outcomes according to event type and exposure pattern.Materials and Methods: This retrospective single-center study included 47 forensic cases with documented inhalational exposure between 2015 and 2025. Data were obtained through retrospective review of forensic reports and available medical records. Cases were assessed in terms of age, sex, event type, exposure pattern, degree of accompanying physical injury, radiological assessment, laboratory findings, hospitalization status, operation status, simple medical intervention status, and life-threatening condition. Appropriate statistical tests were used for group comparisons, and p